Analysis of the Scientific Approach and Higher-Order Thinking Skills (HOTS) in Multimedia Engineering Learning at Vocational High Schools - Ninik Rahayu Ashadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The purpose of this study is to determine the relationship between the implementation of a scientific approach and the development of students’ Higher-Order Thinking Skills (HOTS) in multimedia engineering learning at SMK Handayani. This study uses a quantitative approach with a descriptive correlational method. The sample used in this study consisted of 32 students who took a specialized multimedia engineering subject. Data collection techniques included test observations (pretest and posttest) and documentation. The results of the study show that the average student score increased from 56.25 in the pretest to 82.81 in the posttest. In addition, the highest score increased from 72 to 95, while the lowest score increased from 40 to 68. These results indicate that after learning using a HOTS-oriented scientific approach in the Multimedia Engineering subject, students' abilities showed a clear improvement. Therefore, based on the research findings, it can be concluded that the analysis of the scientific approach and higher-order thinking skills (HOTS) in multimedia engineering learning at SMK is effective. This is evidenced by the increase in the average score from 56.25 in the pretest to 82.81 in the posttest. Furthermore, based on the N-Gain analysis result of 0.61, which falls into the moderate category, it shows that the implementation of the scientific approach is sufficiently effective in improving students' HOTS in Multimedia Engineering learning.